Quantitative extraction of the emission times of high-order harmonics via the determination of instantaneous frequencies - Risoud, François; Caillat, Jérémie; Maquet, Alfred; Taïeb, Richard; Lévêque, Camille (Physical review. A, Atomic, molecular, and optical physics, 2013)
We introduce a method using the concept of instantaneous frequency, as determined with the help of a Hilbert transform, to achieve an accurate time-frequency analysis of the dipole issued from the numerical resolution of the time-dependent Schrödinger equation for any model system driven by an intense laser field. It permits the quantitative extraction of the emission times of the harmonics that coincide with the recollision times of the laser-driven electronic wave packet with the ionic core, for the first and the second return.
Gesehen am 14.01.2022